Pengaruh Kompensasi Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Mediasi Pada PT. Pos Indonesia Kantor Pos Palangka Raya - Ervina Ervina; Ferdinand Ferdinand; Meitiana Meitiana (FKIP, Universitas Palangka Raya, 2023)
This study aims to explain the effect of compensation on employee performance with motivation as a mediating variable at PT. Pos Indonesia Palangka Raya Post Office. The type of research used in this study is associative using quantitative analysis methods. The population in this study were all employees of PT. Pos Indonesia Palangka Raya Post Office. The sample for this study was selected using the Census Sampling technique. The number of samples was 46 people. The research data was collected by statistical data analysis using descriptive analysis and inferential statistical analysis of the Structural Equation Modeling (SEM) model using the Smart Partial Least Squere (SmartPLS) approach as well as validity and reliability tests, the software used was SmartPLS 3.0. The results of the study show that 1) Compensation received by employees affects employee performance. 2) compensation received by employees has a significant positive impact on employee motivation. 3) Motivation has no effect on employee performance at the Palangka Raya Post Office. 4) Motivation is unable to act as a mediating variable for the effect of compensation on employee performance.